Consumer protection in paid crypto training services analysis is based on positive law and Islamic law - Febryan Hidayat; Muttorik Alil Abasir (Priviet Social Sciences Journal, 2026)
The rapid growth of cryptocurrency investment in Indonesia has encouraged the emergence of paid crypto-training services offering investment education and trading guidance. However, concerns arise regarding misleading promotions, inadequate risk disclosure, and the promotion of speculative trading practices that may harm consumers. While previous studies have focused on cryptocurrency regulation and investor protection, limited attention has been given to consumer protection in paid crypto training services from the perspectives of Indonesian positive law and Islamic law. This study aims to analyze consumer protection issues in such services and develop an integrated consumer protection framework. Using normative legal research with statute, conceptual, and comparative approaches, the study examines relevant Indonesian laws and Islamic legal principles. The findings show that misleading advertising, insufficient risk disclosure, and speculative trading signals are the main consumer protection concerns. Both legal systems emphasize transparency, truthful information, accountability, and the prevention of harm. The main contribution of this study is an integrated consumer protection framework consisting of five pillars: transparency, accurate information, risk disclosure, accountability, and prevention of harm. The framework contributes to strengthening consumer protection in digital financial education services.